2018
DOI: 10.4236/pp.2018.94010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antiemetic Agents on Hiccups during Chemotherapy in Patients with Lung Cancer

Abstract: Hiccups commonly occur in patients undergoing chemotherapy for lung cancer and may diminish their motivation for treatment. Therefore, it is important to characterize the hiccups and their risk factors. We examined the medical records of 120 patients with lung cancer during their initial chemotherapy and extracted data on the patients' profiles and the onset, duration, and severity of their hiccup episodes. We found the incidence of hiccups to be 19.2% among the patients. Hiccups appeared within 3 days of begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this study, the steroids methylprednisolone and dexamethasone were identified as risk factors for hiccups in men. Many reports exist on the relationship between steroids and hiccups, yet the mechanism is not clear [9,11,33]. In a study using JADER, a Japanese database, dexamethasone was extracted among steroids as a strong inducer for hiccups [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the steroids methylprednisolone and dexamethasone were identified as risk factors for hiccups in men. Many reports exist on the relationship between steroids and hiccups, yet the mechanism is not clear [9,11,33]. In a study using JADER, a Japanese database, dexamethasone was extracted among steroids as a strong inducer for hiccups [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated drug-induced hiccups. In particular, cisplatin and dexamethasone-used in chemotherapy for cancer treatment-have been reported as important suspect drugs [7][8][9][10]. As there have been no comprehensive risk factor reports on the association between hiccups and medications, we analyzed the medications and patient information associated with hiccups using the Japanese Adverse Drug Event Report database, JADER, through a data mining approach.…”
Section: Introductionmentioning
confidence: 99%